Pengaruh Kompensasi Finansial, Gaya Kepemimpinan, Motivasi Kerja, Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pt. Pei Hai Internasional Wiratama Indonesia - Ismi Fauziyah; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study was conducted to describe financial compensation, leadership style, work motivation, job satisfaction, and the employees performance Pt Pei hai International Wiratama Indonesia know financial compensation influence, leadership style, work motivation, job satisfaction and the employees performance of PT pei hai international wiratama Indonesia. The tool used to know the financial by 78 samples of respondents.As for the data analysis technique using multiple linear regression analysis the results of descriptive analysis show that the employees of PT Pei Hai International Wiratama Indonesia agree on all research variables namely financial compensation, leadership style, work motivation, job satisfaction. The results showed that financial compensation, leadership style, work motivation and job satisfaction simultaneously affect employee performance. Financial compensation variables, leadership style, work motivation, job satisfaction partially affect employee